First-principles thermal transport in amorphous Ge2Sb2Te5 at the nanoscale. Issue 18 (12th March 2021) - Duong, Thuy-Quynh; Bouzid, Assil; Massobrio, Carlo; Ori, Guido; Boero, Mauro; Martin, Evelyne
Abstract : Thermal conductivity of amorphous Ge2 Sb2 Te5 at the nanoscale from first-principles calculations. Abstract : Achieving a precise understanding of nanoscale thermal transport in phase change materials (PCMs), such as Ge2 Sb2 Te5 (GST), is the key of thermal management in nanoelectronics, photonic and neuromorphic applications using non-volatile memories. By resorting to a first-principles approach to calculate the thermal conductivity of amorphous GST, we found that size effects and heat transport via propagative modes persist well beyond extended range order distances typical of disordered network-forming materials. Values obtained are in quantitative agreement with the experimental data, by revealing a strong size dependence of the thermal conductivity down to the 1.7–10 nm range, fully covering the scale of current PCMs-based devices. In particular, a reduction of thermal conductivity as large as 75% occurs for dimensions lying below 2 nm. These results provide a quantitative description of the thermal properties of amorphous GST at the nanoscale and are expected to underpin the development of PCM-based device applications.